2021
DOI: 10.3389/fcell.2021.752718
|View full text |Cite
|
Sign up to set email alerts
|

MCM3AP-AS1: An Indispensable Cancer-Related LncRNA

Abstract: Long non-coding RNAs (lncRNAs) are a class of RNA molecules with transcripts longer than 200 nucleotides that have no protein-coding ability. MCM3AP-AS1, a novel lncRNA, is aberrantly expressed in human cancers. It is significantly associated with many clinical characteristics, such as tumor size, tumor-node-metastasis (TNM) stage, and pathological grade. Additionally, it considerably promotes or suppresses tumor progression by controlling the biological functions of cells. MCM3AP-AS1 is a promising biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In this network, MCM3AP-AS1 was an important lncRNA,which interacted with several miRNAs. MCM3AP-AS1 has been reported to be dysregulated in a variety of cancers, including breast, prostate, and gastric cancers [24]. This study found that MCM3AP-AS1 is upregulated in colorectal cancer, promoting the proliferation, migration, and invasion of colorectal cancer cells, and inhibiting cell apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…In this network, MCM3AP-AS1 was an important lncRNA,which interacted with several miRNAs. MCM3AP-AS1 has been reported to be dysregulated in a variety of cancers, including breast, prostate, and gastric cancers [24]. This study found that MCM3AP-AS1 is upregulated in colorectal cancer, promoting the proliferation, migration, and invasion of colorectal cancer cells, and inhibiting cell apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…MAZ is reported to promote invasiveness of PC cells (40). MCM3AP-AS1 promotes cell migration in PC (41). These factors may cause the upregulation of FOXF2 in PC and FOXF2 perhaps mediates their tumor-promoting effect on PC.…”
Section: Discussionmentioning
confidence: 99%
“…The MCM3AP gene is associated with autosomal recessive peripheral neuropathy, with or without impaired intellectual development (PNRIID). 3 There is increasing evidence to support the MCM3AP gene with autosomal dominant adenomatous polyposis 9,10 and, more recently, hypokalemic periodic paralysis. 2 PNRIID associated with MCM3AP is often caused biallelic pathogenic Two Cases of Periodic Paralysis www.jcnmd.com…”
Section: Discussionmentioning
confidence: 99%
“…Early research connects it to varying forms of cancer. 9,10 It also has been found in individuals with immunodeficiency, 12 intellectual disability, 13 Alzheimer disease, 14 vascular pathologies, [15][16][17] multiple sclerosis, 17 and Charcot-Marie-Tooth disease. 4,[18][19][20] There is preliminary evidence to suggest pleiotropy in the MCM3AP gene responsible for a periodic paralysis phenotype.…”
Section: Clinical Neuromuscular Diseasementioning
confidence: 99%